Towards the improvement of university management - Piórkowska, Natalia Edyta; Ryńca, Radosław (Zielona Góra: Faculty of Economics and Management Press)
In recent decades, the concept of strategic management at universities has attracted more and more attention. There is a significant increase in the awareness of the importance of well-developed development concepts, both among university employees and management staff.
Keywords: strategy implementation; obstacles; university; higher education